Multimodal Media Tools of Popular Geopolitics: Russian Politics in Foreign Media Cartoons - N. K. Radina (Vestnik MGIMO-Universiteta)
The article focuses on the political cartoons about Russia and analyzes the potential of multimodal media texts as the tools of popular geopolitics. The author also employs S. Hall’s concept of propaganda, considering the text of a caricature from semiotic perspective. The integration of the theoretical fields of popular geopolitics and propaganda is substantiated, since political cartoons not only form stereotypes about politics and international relations among media readers, but also perform propaganda functions, broadcasting the point of view of the information platform on Russian politics and Russia. The empirical base of the study embraces 242 political cartoons from Russian-language and English-language foreign media, posted in the public domain on the Internet in 2020-2021, the period of the COVID-19 pandemic. Political cartoons are analyzed with the method of expert evaluation and interdisciplinary classifier for the analysis of political cartoons. The obtained empirical results were subjected to statistical processing, including the identification of correlations. The results demonstrate that in foreign media political cartoons about Russia and Russian politics create two different images of Russia. The first description is typical for English cartoons where Russia appears in the context of international relations, mostly its ties with the United States; and the target character in English cartoon is the Russian president. Englishlanguage cartoons are more often focused on harsh criticism and the use of schematized images. Moderate criticism dominates in Russian-language cartoons of foreign media; the target characters are not only the president, but also other representatives of Russian society. Thematically, Russian-language cartoons are constructed in the context of Russia's internal political problems; the field of education is usually the most intentionally “negative”. According to the study, it is the Russian-language cartoons of foreign media that have the most complex and rich visual code and use Aesopian language. In conclusion, the author highlights the importance of further studies of the tools of popular geopolitics, as well as the need to improve the practice of creating multimodal media texts in the logic of the Russian understanding of geopolitics.